2013
DOI: 10.1007/s12671-013-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Personality Moderate the Effects of Mindfulness Training for Medical and Psychology Students?

Abstract: The majority of mindfulness research to date has reported only on the group-level effects of interventions. Therefore, there is a need to better understand who is most likely to benefit from mindfulness interventions. This study reports on moderation analyses from a two-centre randomised controlled trial of mindfulness-based stress reduction (MBSR) among 288 medical and psychology students. The study investigated whether baseline personality factors (neuroticism, conscientiousness and extroversion) and baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
3
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 39 publications
13
94
3
9
Order By: Relevance
“…Intervention vs AC Combined Combined Plews-Ogan et al, 37 2005 Combined C ombined C ombined Van Ravesteijn et al, 35 2013 Intervention vs AC Combined Combined de Vibe and Moum, 39 2006 Intervention vs PC Combined Posttest Mental Health Intervention: n = 295 Control: n = 234…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention vs AC Combined Combined Plews-Ogan et al, 37 2005 Combined C ombined C ombined Van Ravesteijn et al, 35 2013 Intervention vs AC Combined Combined de Vibe and Moum, 39 2006 Intervention vs PC Combined Posttest Mental Health Intervention: n = 295 Control: n = 234…”
Section: Findings In Contextmentioning
confidence: 99%
“…Intervention vs AC Combined Combined Plews-Ogan et al, 37 2005 Combined C ombined C ombined Van Ravesteijn et al, 35 2013 Intervention vs AC Combined Combined de Vibe and Moum, 39 observed a moderate effect size when comparing MBIs with wait list controls, but this effect was small when compared with active controls, and even smaller when including psychotherapy. The authors concluded that MBIs did not differ from cognitive behavior therapies or pharmacotherapy.…”
Section: Posttestmentioning
confidence: 99%
“…No negative effects of mindfulness were reported, but some individuals found it more effective than others. De Vibe et al (2015) explored whether certain personalities are more likely to benefit from mindfulness interventions. They conducted a randomised controlled trial of mindfulness-based stress reduction on 288 medical and psychology students.…”
Section: Discussionmentioning
confidence: 99%
“…6 Standardised programmes such as Mindfulness-based Stress Reduction have also proved to benefit personality traits of neuroticism. 7 Determining the differentiated influence of these psychological traits and processes in explaining anaesthetists' stress outcomes is a key step in the development of interventions to improve stress and burnout management. Therefore, in future studies of burnout in anaesthetists, mindfulness and self-compassion traits should be evaluated.…”
Section: Editormentioning
confidence: 99%
“…5 Also people experience personal growth and develop during their professional life, but the ease in which they naturally adopt stress-relieving strategies or learn psychological means to regulate stress will be dependent on the type of person they are to begin with. 6,7 So individual susceptibility remains an important factor in the development of burnout. Of course, as an instrument of selection, the 'Big Five' personality trait model may be too general to use in the selection of future anaesthesiologists, let alone exclude them from the training programme.…”
Section: Editormentioning
confidence: 99%